Cadmium Uptake by Ryegrass and Ryegrass–Clover Mixtures under Different Liming Rates. Issue 5 (1st September 2018) - Benyas, Ebrahim; Owens, Jennifer; Seyedalikhani, Salome; Robinson, Brett
Abstract : Cadmium accumulates in soils that receive repeated applications of Cd‐rich superphosphate fertilizers. There is evidence that adding clovers to a crop solubilizes soil Cd, increasing the bioavailability of Cd. This can lead to high plant Cd concentrations. This research aimed to test whether liming‐induced increases in pH in mixed crops of clovers and ryegrasses reduced forage Cd concentrations. A greenhouse pot trial applied lime at three rates (0, 1, and 2% of soil dry weight) to eight different plant treatments—four as monocultures (perennial ryegrass [ Lolium perenne L.], Italian ryegrass [ L. multiflorum Lam.], white clover [ Trifolium repens L.], and red clover [ T. pratense L.]) and four as ryegrass–clover mixtures (two plant types in each treatment)—in soil (initial soil pH = 5.1, initial soil Cd concentration = 1.31 mg kg −1 ) with added Cd (CdSO4 ∼ 1 mg kg −1 ). Adding lime increased soil pH in both mono‐ and mixed crops and, in most treatments, increased forage yields. However, the relationship between forage Cd and soil pH differed between plant treatments. In mono‐ and mixed crop treatments containing perennial ryegrass, adding lime increased the forage yield but did not increase the mass of Cd in the plants compared with the no‐lime treatment. However, adding lime to treatments that included Italian ryegrass increased both the forage yield and the Cd compared with the no‐lime treatment. The results show that a combination of certain plant species composition and lime rates can optimize forage yields without increasing forage Cd concentrations. Core Ideas: Liming increased plant yield in all plant treatments. Liming decreased plant Cd uptake in mixed crops that included perennial ryegrass. Liming increased plant Cd uptake in mixed crops that included Italian ryegrass Managing Cd uptake requires the correct pairing of lime with both soil and pasture.